PENGARUH PERSEPSI HARGA DAN CITRA MEREK TERHADAP MINAT BELI PRODUK MOTOR MEREK YAMAHA NMAX DI KOTA PALU - Desyani, Eka (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to determine the influence of price perceptions and brand image on the interest in purchasing Yamaha NMAX in Palu City. Type of stduy is explanatory. Population consist of people in Palu City who have known and interested, but do not yet have Yamaha NMAX products. Sampling technique is purposive sampling, with total samples of 90 people. Data collection using questionnaire which then processed by using regression analysis tool with SPSS for Windows Release 16.0. Method of analysis is multiple regression analysis. The result shows that price perceptions have positive and significant influence on the interest of poeople purchasing Yamaha NMAX in Palu City, with significance level t-sig. of (0,05 ? 0.041) with regression coefficient equals to 0.154. Brand image has positive and significant influence on the interest of buying Yamaha NMAX in Palu City, with significance level t sig. of (0,05 ? 0.000) with regression coefficient value equals to 0.464.